2004
DOI: 10.1002/pssb.200409080
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of persistent luminescence in Sr2MgSi2O7:Eu2+; Dy3+

Abstract: Persistent luminescence is the phenomenon that a phosphor after exposure to UV-light (day light) shows visible luminescence in the dark that persists during the whole night (≈ 10 hours). In 1996 a mechanism was proposed by Matsuzawa et al. [1] In order to develop a better mechanism it is necessary to know the location of the levels of Eu and Dy relative to the top of the valence band and the bottom of the conduction band. Recently a new method has become available to construct a scheme with the level location… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(74 citation statements)
references
References 14 publications
(23 reference statements)
3
69
1
1
Order By: Relevance
“…These oxygen vacancies are the major contributors to the phosphorescence behavior of many oxide based phosphors. For a suitable trap depth, the trap concentration is directly depends on the cerium ions [42,43]. It is reported that a suitable trap depth (0.65-0.75 eV) is essential for phosphors to show long persistence.…”
Section: Cie Chromaticity Coordinatementioning
confidence: 99%
“…These oxygen vacancies are the major contributors to the phosphorescence behavior of many oxide based phosphors. For a suitable trap depth, the trap concentration is directly depends on the cerium ions [42,43]. It is reported that a suitable trap depth (0.65-0.75 eV) is essential for phosphors to show long persistence.…”
Section: Cie Chromaticity Coordinatementioning
confidence: 99%
“…Nevertheless, this model can be used for the interpretation of many interesting chemical, physical and spectroscopic properties of rare-earths [74]. This model was also suggested [75] to solve the enhancement of persistent luminescence by the RE 3+ co-dopants in Sr 2 MgSi 2 O 7 :Eu 2+ . It seems now [67] that the defects due to charge compensation originating from the aliovalent substitution of Sr 2+ by RE 3+ leads to a multitude of defects overruling the rare-earth ions as traps to store the excitation energy in the charging phase of the persistent luminescence mechanism.…”
Section: Positions Of 4f N Levels In the Sr 2 Mgsi 2 O 7 Host Band Stmentioning
confidence: 99%
“…However, there is a common model for the Eu 2+ and Dy 3+ co-doped long-lasting phosphors that suggests the Dy 3+ ions as hole-trapped to form Dy 4+ , which has been doubted by several researchers [13,14]. In contrast, our suggestion is more reasonable.…”
Section: Trap Center Effect Of Dy 3+mentioning
confidence: 49%
“…It has been suggested that Dy 3+ ions act as trap centers in many long-lasting phosphors doped with Eu 2+ and Dy 3+ [13]. Thus we consider that the function of Dy 3+ ions is the same in MgSiO 3 :Eu 2+ , Dy 3+ , Mn 2+ .…”
Section: Trap Center Effect Of Dy 3+mentioning
confidence: 97%